Information counseling in hiv/aids prevention for the community at the ridus labuang baji outpatient pharmacy - Alim, Nur; Sarifah, Latifah Mahaya; Nurta’jia, Nurta’jia; Trisnawati, Trisnawati; Muhammad, Saina (CV. Paperhome Indonesia, 2024)
Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms of disease caused by the Human Immunodeficiency Virus (HIV). HIV damages the human immune system, making the body susceptible to other diseases that can be fatal. In people with normal immune systems, these diseases usually do not cause significant disorders. The purpose of the activity is to provide information about AIDS prevention measures to patient families at the Outpatient Pharmacy of Labuang Baji Hospital. The type of activity is direct counseling and distribution of information brochures containing information related to HIV-AIDS prevention. From the results of the counseling that has been carried out, it can be concluded that the knowledge of patient families at the Outpatient Pharmacy of Labuang Baji Hospital about HIV-AIDS prevention is excellent because respondents can understand HIV-AIDS starting from knowing the characteristics of HIV/AIDS, causes, how the disease is transmitted, and how to prevent it.